Potential Changes in Watermelon (Citrullus lannatus) Ploidy Treated By Colchicine - Handayani, Rd. Selvy; Yusuf, Muhamad; Akmal, Ajmir (Journal of Tropical Horticulture, 2018)
The purpose of this study was to determine the effect of colchicine on changes in ploidy watermelon. The research was conducted in Agroecotechnology laboratory Universitas Malikussaleh, Microtechnique laboratory Agronomy and Horticulture Departement, Bogor Agricultural University, and Beuringen, Murah Mulia subdistrict, North Aceh. This research used Completely Randomized Design (CRD) two factors. The first factor was watermelon seed soaking time in colchicines 0,02% ie.0, 24,36, and 48 hours. The second factor was the concentration of the colchicine solution on the sprout growth point i.e. 0, 0,1, and 0,2 %. The results showed that plants were given colchicine became to shorter and fewer number of leaves than plants without any treatment. Colchicine could increase the size of the stomata, but it did not change the shape of stomata. Plants that were given colchicine had the potential to ploidy multiplication.